Real-time and long-time in vivo imaging in the shortwave infrared window of perforator vessels for more precise evaluation of flap perfusion. (October 2016) - Feng, Shaoqing; Chen, Jun; Wo, Yan; Li, Yunxia; Chen, Shiyi; Zhang, Yixin; Zhang, Wenjie
Abstract: Effective real-time and long-time in vivo imaging for flap perfusion requires bright and stable imaging agents whose emissions can effectively penetrate live tissues without photobleaching. Compared to the standard imaging agent today – intraoperative indocyanine green (ICG), quantum dots (QDs) is a more attractive alternative due to its excellent optical properties including broad emission spectrum and stability against photobleaching. Recent studies have confirmed that the shortwave infrared window (SWIR) between 1000 and 2300 nm is the most sensitive spectral range for in vivo imaging due to its extremely low tissue absorption and autofluorescence. Here, we, for the first time, report a novel approach of flap perfusion assessment that provides real-time and long-time in vivo imaging using lead sulfide (PbS) QDs. Our results show that PbS QDs, as an imaging agent, can improve the stability of in vivo high-resolution images in a sustained manner, thus facilitating the precise evaluation of flap perfusion. In summary, compared to current imaging reporters, SWIR QDs have high photostability and deep tissue penetration, which makes them as promising in vivo imaging agents for more precise evaluation of flap perfusion.